Knowledge, Attitudes, and Practices Regarding Swallowing Disorders Among General Practitioners - Zou M; Zhu X; Li J; Yu H; Guo P (International Journal of General Medicine)
Min Zou,1,* Xingzhi Zhu,2,* Juan Li,1 Huan Yu,1 Peipei Guo1 1Guizhou Provincial People’s Hospital, Guiyang, Guizhou, 550002, People’s Republic of China; 2The First People’s Hospital of Guiyang, Guiyang, Guizhou, 550002, People’s Republic of China*These authors contributed equally to this workCorrespondance: Juan LiGuizhou Provincial People’s Hospital, Guiyang, Guizhou, 550002, People’s Republic of China, Tel +8613885186730, Email 694807055@qq.comBackground: Swallowing disorders constitute a significant clinical concern, necessitating effective management and early detection. General practitioners (GPs) play a pivotal role in identifying and referring patients with swallowing disorders, emphasizing the importance of assessing their Knowledge, Attitudes, and Practices (KAP) in this domain.Methods: A cross-sectional study was conducted between July and October 2023, involving general practitioners who completed a self-administered questionnaire containing demographic information and KAP assessment.Results: The final analysis included 365 participates, with 242 (66.3%) completed by female participants and 106 (29.04%) by individuals with 5– 10 years of professional working experience. The mean scores for knowledge, attitude, and practice were 12.41 ± 4.202 (possible range: 0– 18), 22.25 ± 2.06 (possible range: 6– 30), and 32.81 ± 9.48 (possible range: 10– 50), respectively. Knowledge was demonstrated a positive correlation with attitude (r = 0.329, P < 0.001) and practice (r = 0.375, P < 0.001), while attitude also showed a positive correlation with practice (r = 0.309, P < 0.001). According to multivariate analysis, knowledge (OR = 1.13, 95% CI: [1.07– 1.20], P < 0.001) and attitude (OR = 1.19, 95% CI: [1.05– 1.36], P = 0.005) were independently associated with proactive practice.Conclusion: General practitioners demonstrated moderate knowledge, attitudes, and practices regarding swallowing disorders. Targeted educational interventions are essential to enhance general practitioners’ knowledge regarding swallowing disorders.Keywords: knowledge, attitudes, practices, swallowing disorders, general practitioner, cross-sectional study